Avaliação da participação de grânulos de estresse na resposta a agentes antineoplásicos em linhagens celulares de tumores cerebrais - Fabrício de Almeida Souza Vilas Boas (2015)
Malignant gliomas are one of the most lethal types of brain tumors. Even after surgical resection, have high risk of recurrence, are refractory to most known treatments and, even after intensive care, the patient usually dies within 12 to 15 months. Standard treatment consists of surgery, followed by radiation therapy and chemotherapy with antineoplastic agents. Due to frequent chemoresistance, the study of new therapeutic targets is paramount in order to maximize the effects of treatments without harming the patient. When the cells are exposed to hostile conditions (i.e., hypoxia, lack of nutrients and drugs), the translation of messenger RNA (mRNA) is stopped. The polyssome-free untranslated mRNA will then bind to specific proteins to assemble stress granules (SG) which are involved in regulating the translation of specific mRNA. Interfering with SG formation process, therefore, may be an effective strategy to sensitize glioma cells. Thus, the aim of this study was to evaluate the role of SG in glioma cell resistance [cell lines C6 (rat glioma) and U87MG (human glioblastoma)] to antineoplastic agents. For this, we used two approaches. The first one was the use of a plasmid containing a dominant negative form of the alpha subunit of eukaryotic initiation factor 2 (eIF2αDN), in order to reduce eIF2α phosphorylation levels, which is one of the main sensors of cell stress and subsequent activation of the assembly of SG. The second approach was the use of the RNA interference technique for silencing the G3BP1 expression, a major component of SG. We demonstrated that Bortezomibe, Cisplatin and Etoposide stimulate phosphorylation eIF2α and induce the formation of SG in both glioma cell lines. Furthermore, by using the plasmid containing eIF2αDN, eIF2α phosphorylation was reduced by about 30% and the ability of cells to form SG was significantly reduced following exposure to the anticancer agents. This was associated with greater reduction in cell viability and induction of apoptosis. The approach using siRNA to impairing G3BP1 expression was able to reduce the the protein levels by about 50% and the ability of U87MG cells of forming SG was also significantly reduced. This was associated with greater reduction in cell viability of cells exposed to at least one of three siRNA tested. Our data suggest that stress granules play an important role in the resistance of brain tumor cells to antineoplastic agents.